Chromosomal Composition of Aneuploid Clones with Different DNA Contents in Head and Neck Squamous Cell Carcinomas as Determined by Combined Flow Cytometry and Fluorescence In Situ Hybridization - Joerg Hemmer; Carmen Hauser (Analytical Cellular Pathology)
Studies with DNA flow cytometry (FCM) have shown that DNA contents of aneuploid tumour clones vary in a wide range. The aim of this study was to analyse whether homologous chromosomal changes exist despite the individual differences that may be of general relevance for the development of gross aneuploidy in squamous cell carcinomas of the head and neck. Fluorescence in situ hybridization (FISH) with 13 centromere‐specific DNA probes was applied to 3 diploid and 11 aneuploid tumours with DNA indices ranging between 0.8 and 2.2. Disomic and monosomic cell populations were prevalent findings in DNA‐diploid tumours. Polysomies were common in aneuploid tumours. Different degrees of aneusomy for identical chromosomes were recurrent features in aneuploid tumours. FISH signal heterogeneity was identified for all chromosomes. The mean number of aneusomic cell populations identified for DNA‐aneuploid tumours ranged between 1.6 for chromosome 17 and 3.1 for chromosome 3. Inconsistencies between FISH and FCM data may indicate that centromere‐specific DNA probes identify gains and losses of marker DNA due to complex karyotypic rearrangements rather than absolute changes in chromosome numbers. Overall, there was no evidence of the critical involvement of particular chromosomes in the development of different DNA contents.